Versatile Synthesis of Pd−M (M=Cr, Mo, W) Alloy Nanosheets Flower‐like Superstructures for Efficient Oxygen Reduction Electrocatalysis. Issue 16 (22nd June 2020) - Zhang, Xiaoshu; Fan, Jiayao; Han, Min; Zhao, Shulin; Lu, Linzhi; Xu, Dongdong; Lin, Yue; Shi, Naien; Liu, Ying; Lan, Ya‐Qian; Bao, Jianchun; Dai, Zhihui
Abstract: Pd‐based nanoalloys are promising electrocatalysts for replacing Pt‐based ones toward oxygen reduction reaction. Despite that great progress has been achieved, universally synthesizing Pd‐based alloy nanosheets and further integrating them into porous or hierarchical superstructures remain a challenge, and their ORR performances are not systematically investigated. Herein, novel ultrathin and highly wrinkled Pd−M (M=Cr, Mo, W) alloy nanosheets flower‐like superstructures (NSFSs) are universally fabricated via a polyether and small molecules/ions ligand assisted solvothermal method. Such Pd−M NSFSs possess mesoporous structures and co‐exist single‐atom‐like and cluster‐like M species on their surfaces. Compared with pure Pd NSFSs, those Pd−M NSFSs show greatly enhanced ORR activity in alkaline media. Due to the unique microstructure feature, proper alloy constituent and stronger interatomic polarization or electronic coupling, the Pd−W NSFSs show the highest ORR activity with the half‐wave potential of 0.89 V ( vs . RHE) and mass activity of 0.46 A mgPd −1 at 0.90 V ( vs . RHE), outperforming commercial Pt/C, and most of reported Pd(or Pt)‐based catalysts. Moreover, the Pd−W NSFSs manifest outstanding durability and anti‐CO poisoning ability yet. This work may spur the development of 2D Pd‐based nanoalloy superstructures and promote their applications in fuel cells or other clean energy fields. Abstract : Catalysis in bloom : Novel Pd−M (M=Cr, Mo, W) alloy nanosheets flower‐like superstructures (NSFSs) have been universally fabricated for the first time through a polyether and small molecules/ions ligands assisted solvothermal strategy. Due to the unique microstructural feature, proper alloy constituent and stronger interatomic polarization, the Pd−W NSFSs manifest exceptional electrocatalytic performance toward oxygen reduction reaction, outperforming Pd−Cr and Pd−Mo NSFSs, Pt/C, and most of other reported Pd(or Pt)‐based electrocatalysts.